Literature Review Effect of Workload and Compensation on Job Statisfaction and Their Impact on Employee Performance - Sherly Shinta Emalia (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews Determination Job satisfaction and Employee Performance: Analysis Workload and Compensation , A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research . The result of this research library is that: 1) Workload effect on Job satisfaction ; 2) Compensation effect on Job satisfaction ; 3) Workload effect on Employee Performance; 4) Compensation effect on Employee Performance; and 5) Job Satisfaction effect on Employee Performance.